The Impact of Transformational Leadership, Motivation, and Organizational Commitment on Employee Performance: Case study at the Village and Customary Community Empowerment Service of Papua Province - Tokoro, Silce Yonice; Srem, Ade Irma A.; Wanma, Johanis R. (Magister Manajemen Universitas Cenderawasih, 2025)
This study aims to analyze the influence of leadership, motivation, and organizational commitment on employee performance at the Village and Customary Community Empowerment Service of Papua Province. A quantitative descriptive approach was used, with data collected through questionnaires, interviews, and observations. The sample consists of 52 randomly selected employees. The results of multiple regression analysis show that leadership has a positive and significant impact on employee performance (p < 0.05), while motivation and organizational commitment do not show significant partial effects. However, all three variables simultaneously have a significant impact on employee performance. The implication of these findings is the importance of effective leadership management as well as the management of motivation and organizational commitment to improve employee performance in the public sector.